SMES information needs and the digital library - Poon, Sook Yee (2008)
Greater attention is now paid to the growing informaton needs of Small and Medium Enterprises (SMEs) especially with the rapid growth of economy in Asia Region. In addition, with IT becoming part and parcel of our life, the traditional library is currently undergoing a transformation to fulfil our thirst for more information. This research study the application of Digital Library (DL) on the information needs of SMEs in Singapore by analysing the concept of DL and the information shortage faced by SMEs.